Mobile Text Messaging for Tobacco Risk Communication Among Young Adult Community College Students: Randomized Trial of Project Debunk - Alexander V Prokhorov; Karen Sue Calabro; Ashish Arya; Sophia Russell; Katarzyna W Czerniak; Gabrielle C Botello; Minxing Chen; Ying Yuan; Adriana Perez; Damon J Vidrine; Cheryl L Perry; Georges Elias Khalil (JMIR Publications, 2021)
BackgroundThe use of new and emerging tobacco products (NETPs) and conventional tobacco products (CTPs) has been linked to several alarming medical conditions among young adults (YAs). Considering that 96% of YAs own mobile phones, SMS text messaging may be an effective strategy for tobacco risk communication. ObjectiveProject Debunk is a community-based randomized trial aiming to identify specific types of messages that effectively improve perceived NETP and CTP risk among YAs in community colleges. MethodsWith YAs recruited offline from 3 campuses at the Houston Community College (September 2016 to July 2017), we conducted a 6-month randomized trial with 8 arms based on the combination of 3 message categories: framing (gain-framed vs loss-framed), depth (simple vs complex), and appeal (emotional vs rational). Participants received fully automated web-based SMS text messages in two 30-day campaigns (2 messages per day). We conducted repeated-measures mixed-effect models stratified by message type received, predicting perceived CTP and NETP risks. Owing to multiple testing with 7 models, an association was deemed significant for P<.007 (.05 divided by 7). ResultsA total of 636 participants completed the baseline survey, were randomized to 1 of 8 conditions (between 73 and 86 participants per condition), and received messages from both campaigns. By the 2-month post campaign 2 assessment point, 70.1% (446/636) completed all outcome measures. By the end of both campaigns, participants had a significant increase in perceived NETP risk over time (P<.001); however, participants had a marginal increase in perceived CTP risk (P=.008). Separately for each group, there was a significant increase in perceived NETP risk among participants who received rational messages (P=.005), those who received emotional messages (P=.006), those who received simple messages (P=.003), and those who received gain-framed messages (P=.003). ConclusionsIn this trial, YAs had an increase in perceived NETP risk. However, with stratification, we observed a significant increase in perceived NETP risk upon exposure to rational, emotional, simple, and gain-framed messages. In addition, YAs generally had an increase in perceived CTP risk and presented nonsignificant but observable improvement upon exposure to emotional, complex, and loss-framed messages. With the results of this study, researchers and practitioners implementing mobile health programs may take advantage of our tailored messages through larger technology-based programs such as smartphone apps and social media campaigns. Trial RegistrationClinicalTrials.gov NCT03457480; https://clinicaltrials.gov/ct2/show/NCT03457480 International Registered Report Identifier (IRRID)RR2-10.2196/10977